CHANGES IN THE ELECTROLYTE BALANCE IN DOGS WITH THE ONLY LEFT KIDNEY UNDER THE CONDITIONS OF LOW AND HIGH MOUNTAINS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
We studied 22 mature male dogs weighing 10-14 kg: 10 intact, 6 nephrectomized and 6 dogs with a single resected kidney. Observations were carried out at the Anzob pass (altitude 3500 m a.s.l.) and in Dushanbe (altitude 850 m a.s.l.) after unilateral nephrectomy (6 dogs). The concentration of sodium and potassium in plasma, erythrocytes and urine, creatinine and residual nitrogen in the blood, and minute diuresis were determined. It has been established that in conditions of high mountains, the compensatory capabilities of the kidney are sharply suppressed. The combined effect of stress factors caused a breakdown of the “sodium pump” mechanism, which contributed to the accumulation of sodium ions in erythrocytes and urine, and a decrease in its clearance and excreted fraction. The shift in potassium balance after nephrectomy was insignificant, with the exception of the clearance, which decreased only in the initial periods after the operation. All these violations indicate that the ion-regulating function in the remaining kidney is not fully restored one month after the operation.  It was noted that the dynamics of changes in the functional activity and electrolyte balance of a single kidney during the readaptation period is the same as during the stay of animals in the highlands, there are differences only in the severity of individual indicators.
Keywords: adaptation, high mountains, potassium, sodium, nephrectomy, resected kidney, readaptation.